Ormož : Utrjeno naselje iz pozne bronaste in starejše železne dobe = Befestigte Siedlung aus der späten Bronze- und der älteren Eisenzeit - Dular, Janez; Tomanič-Jevremov, Marjana (2010)
Ormož ranks among the most important archaeological sites in Slovenia. The fortified settlement from the Late Bronze and Early Iron Age extended over the area where the town stands today. It developed on a high-lying terrace on the left bank of the river Drava, which forms a broad bend right at the foothills. This site was intentionally selected, since towards the river it was protected by a steep slope, and to the east and west by relatively deep natural dykes. In the present monograph a survey is given of the results of the excavations which were carried out in Ormož during the period from 1974 to 1981.